Revaluation Effect of Auditor Switch in Malaysia and its Determinants - Aliahmed, Huson Joher (2000)
A body of accounting literature has grown on the phenomena of auditor switches mostly in developed countries from the research by academics, accounting professionals and industry experts because of its strategic implication for a firm value, credibility of financial reporting and the cost of monitoring management activities. Despite the growing concerns shown in the developed economies about the consequence of auditor switches, which are associated with substantial direct and indirect costs, little attempt appears to have been made in Malaysia to examine the possible reasons for changing auditors or to estimate the shareholders wealth implication. Thus, the objective of this study is to make a start in examining this very significant accounting activity in a fast developing Malaysian economy, perhaps, to serve as an example of more studies in emerging countries. The particular objectives are (a) to ascertain determinants of auditor switch in Malaysia, (b) to examine the hypothesised relationship between the changes in firms' characteristics and choice of quality differentiated audit firms and (c) to ascertain the share valuation effect of auditor switches in Malaysia. Audit firms are clearly ranked as belong to a higher and lower prestige category in this country, which enables, it is hoped, a search for the revaluation effect.